Letter (copy) : Food and medical supplies for Spain
029-0111-001 FC/EK/1228. Secretary's 19th July, 1937. Miss E. Wilkinson, Spanish Women's Committee for Help to Spain, 16, Lloyd's Square, London, W.C.1. Dear Madam, Food and Medical Supplies for Spain In the absence of Mr. Tewson I am acknowledging receipt of your letter of the 15th instant regarding the foodstuffs and medical supplies sent to Spain. We are expecting Mr. Tewson back in the office on Monday next, when your letter will be placed before him. Yours faithfully, 292/946/29/111